"Hoping for life means waiting for death": Emotional anchoring and themata in media reporting on paediatric organ donation. (19th May 2021) - Norton, Maddison; Moloney, Gail; Sutherland, Michael; Sargeant, Sally; Bowling, Alison
Abstract: Paediatric organ donation rates in Australia do not match the demand for paediatric organ transplants. Paediatric donations require parents to consent to donate the organs of their child, yet little research exists on how paediatric donation is understood outside of the medical world. Drawing from social representation theory, we examined how paediatric donation was portrayed by the media, the primary source of information about organ donation. Fifty‐nine newspaper articles, across eight Australian newspapers, were subjected to thematic analysis. Common themes coalesced around the paediatric donation decision, what the decision means for parents, and the experiences of paediatric transplant recipients and their families. Donation and transplantation were portrayed either as a contradiction, where a child was required to die in order for a child to live, or as mutually beneficial, where donation was a positive outcome of a tragic death. Interpreted within a dialogical framework, we suggest that notions of contradiction and mutual benefit are generated by the underlying thema life/death, and shaped in tandem by the paediatric context. The roles of themata, emotional anchoring, and objectification are discussed. Importantly, this study highlights the need to investigate the interplay between emotional contradiction, mutual dependence, and parental decision‐making about paediatric organ donation.